2013
DOI: 10.1158/1055-9965.epi-13-0239
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Microsatellite Instability in Colorectal Cancer: A Population-based Study

Abstract: Background: Previous studies reported a positive association of body mass index (BMI) with microsatellitestable (MSS) but not with microsatellite-instable (MSI-high) colorectal cancer. However, information from population-based studies conducted in representative age groups is so far limited.Methods: We conducted a population-based case-control study (DACHS) in Southern Germany, including 1,215 patients with incident colorectal cancer and 1,891 matched controls with no upper age limit. Information on risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 33 publications
2
31
1
1
Order By: Relevance
“…While high BMI is a consistent and convincing risk factor for colorectal cancer overall (relative risks in the range of 1.3 to 1.5 are common for an obese BMI relative to a normal BMI), MPE studies have overall suggested that the associations are stronger for, or even restricted to, non-MSI colorectal cancer (relative risks up to around 2 are common for an obese BMI relative to a normal BMI). [11, 33, 8284] Other recent studies have shown that these results might be corroborated with expression status of FASN,[99] which has been associated with MSI-high in colorectal cancer. [100] These data also indicate the existence of molecular confounding in MPE, and a need for new methodologies to disentangle correlated molecular biomarkers.…”
Section: Colorectal and Breast Cancersmentioning
confidence: 87%
See 1 more Smart Citation
“…While high BMI is a consistent and convincing risk factor for colorectal cancer overall (relative risks in the range of 1.3 to 1.5 are common for an obese BMI relative to a normal BMI), MPE studies have overall suggested that the associations are stronger for, or even restricted to, non-MSI colorectal cancer (relative risks up to around 2 are common for an obese BMI relative to a normal BMI). [11, 33, 8284] Other recent studies have shown that these results might be corroborated with expression status of FASN,[99] which has been associated with MSI-high in colorectal cancer. [100] These data also indicate the existence of molecular confounding in MPE, and a need for new methodologies to disentangle correlated molecular biomarkers.…”
Section: Colorectal and Breast Cancersmentioning
confidence: 87%
“…Dr. Ogino presented an introductory lecture on MPE, emphasizing its strengths, opportunities, and challenges. MPE research has shown that smoking and obesity are risk factors for different subtypes [microsatellite instability (MSI) and non-MSI subtypes, respectively] of colorectal cancer,[11, 33, 7484] which is a single entity in conventional epidemiology. This paradigm shift is important in cancer prevention.…”
Section: Overview Sessionmentioning
confidence: 99%
“…Screening for the levels of MIN in tissues results in the latter as having a microsatellite-stable (MSS) or microsatellite-instable (MSI) profile. Studies have shown that obesity is linked with an increased risk of microsatellite high (MSI-H) colorectal cancer in women [113]. In endometrial cancer, an MSI profile was associated with a high BMI [114].…”
Section: Cellular Instability and Changes In Cellular Energetics Linkmentioning
confidence: 99%
“…All patients had a histologically confirmed first diagnosis of primary CRC and were eligible for recruitment if they were at least 30 years old, physically and mentally able to participate in an interview, sufficiently proficient in German language and resident in the study region. More details about patient recruitment and tissue processing in the DACHS study have been previously reported [17,18]. Of 1975 CRCs diagnosed in 2003-2007 and enrolled in DACHS, 427 had been histologically investigated and TNM classified at the Institute of Pathology, University of Heidelberg, and were included in this study.…”
Section: Study Populationmentioning
confidence: 99%